Chinese Customs Regulations on Cross-Border E-Commerce: A Growth Opportunity for Foreign Enterprises and Chinese Commercial Platforms - Ruiz, Miriam (Sinología hispánica. China Studies Review, 2018)
The fast improvement of communications since 1980´s has sped up the way of world-wide consumption. The embrace of globalization and all the changes and improvements that come with it, such as new technologies, faster and more accessible routes and ways of transportation, have created a new way to sell and buy goods named electronic commerce or e-commerce.This new way of commerce was officially adopted in May, 1998 in the Declaration on Global Electronic Commerce of the Second Ministerial Conference of the World Trade Organization, which recognizes the growth of this new way of trade and the new opportunities it brings with. Since then, the term of electronic commerce, or e-commerce, is understood as to mean the production, distribution, marketing, sale or delivery of goods and services by electronic means1. Even if today e-commerce is not a new subject, we can say it has become a popular and stable way of consumption, job, and income source, not only for the seller and buyer, but also for all the intermediaries involved in the process. In this article, the characteristics of cross-border e-commerce and its implication on Chinese Customs legislations and commercial platforms will be analyze by noting their main characteristics and the challenges shared for development, as well as the effects they generate among consumers, enterprises and the government.